Magmatic gas percolation through the old lava dome of El Misti volcano - Moussallam, Yves (2017)
The proximity of the major city of Arequipa to El Misti has focused attention on the hazards posed by the active volcano. Since its last major eruption in the fifteenth century, El Misti has experienced a series of modest phreatic eruptions and fluctuating fumarolic activity. Here, we present the first measurements of the compositions of gas emitted from the lava dome in the summit crater. The gas composition is found to be fairly dry with a H2O/SO2 molar ratio of 32 ± 3, a CO2/SO2 molar ratio of 2.7 ± 0.2, a H2S/SO2 molar ratio of 0.23 ± 0.02 and a H2/SO2 molar ratio of 0.012 ± 0.002. This magmatic gas signature with minimal evidence of hydrothermal or wall rock interaction points to a shallow magma source that is efficiently outgassing through a permeable conduit and lava dome. Field and satellite observations show no evolution of the lava dome over the last decade, indicating sustained outgassing through an established fracture network. This stability could be disrupted if dome permeability were to be reduced by annealing or occlusion of outgassing pathways. Continued monitoring of gas composition and flux at El Misti will be essential to determine the evolution of hazard potential at this dangerous volcano.